The impact of hyperthermia after acute carbon monoxide poisoning on neurological sequelae. (April 2019) - Moon, JM; Chun, BJ; Lee, SD; Shin, MH
This study investigated whether hyperthermia within the first 24 h after presentation was associated with long-term neurological outcomes after acute carbon monoxide (CO) poisoning. This retrospective study included 200 patients with acute severe CO poisoning. Hyperthermia (≥ 37.5°C) developed during the first 24 h after presentation in 55 (27.5%) patients, and poor long-term neurological sequelae assessed at 23 months after acute CO poisoning developed in 19.5% of the patients. The incidence of poor long-term neurological outcomes was significantly higher in the hyperthermia group than in the normothermia group. Patients with poor long-term neurological outcomes had higher maximum temperatures than patients with good outcomes. No significant difference was found in the time of hyperthermia onset within the first day according to the neurological outcomes. Hyperthermia (adjusted odds ratio (aOR) 5.009 (95% confidence interval (CI) 1.556–16.126)) and maximum temperature (aOR 2.581 (95% CI 1.098–6.063)) within the first 24 h after presentation to the emergency department were independently associated with poor long-term neurological outcomes. Body temperature measurements, which are easily and noninvasively recorded at the bedside in any facility, help to predict the risk for poor long-term neurological outcomes. This study carefully emphasizes fastidious control of pyrexia, particularly during the early period after acute CO poisoning.